1986
DOI: 10.3758/bf03200069
|View full text |Cite
|
Sign up to set email alerts
|

Effects of motor activity on the elicitation and modification of the startle reflex in rats

Abstract: In order to examine the effects of efferent processes on the elicitation and modification of startle behavior, we administered startle-eliciting stimuli to rats while they were engaged in spontaneous motor activity. When tone bursts (Experiment 1) or electric shocks (Experiment 2) were used to elicit the reflex, its amplitude was substantially less when the rats were active than when they were quiet. Grooming, face washing, and consuming were associated with the greatest reduction. The ability of a 50-dB audit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

1988
1988
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 23 publications
2
19
1
Order By: Relevance
“…Despite the prediction of circadian regulation of PPI in male rats based on the activity dependent reduction in the ability of a prepulse to inhibit a subsequent startle response as reported by Wecker and Ison (1986), circadian regulation of PPI in male rats was not found when PPI was measured in a 4 hour time frame between 2-6 hours after lights on or off (Weiss et al, 1999). In accordance with these results, we report no significant overall effect of light status (i.e.…”
Section: Discussionsupporting
confidence: 79%
“…Despite the prediction of circadian regulation of PPI in male rats based on the activity dependent reduction in the ability of a prepulse to inhibit a subsequent startle response as reported by Wecker and Ison (1986), circadian regulation of PPI in male rats was not found when PPI was measured in a 4 hour time frame between 2-6 hours after lights on or off (Weiss et al, 1999). In accordance with these results, we report no significant overall effect of light status (i.e.…”
Section: Discussionsupporting
confidence: 79%
“…Previous work has indicated that motor activity may decrease startle reactivity and also PPI (Wecker and Ison 1986;Plappert et al 1993). Whereas in particular grooming had a strong effect, gross postural changes, such as turning, did not affect startle and PPI (Wecker and Ison 1986).…”
Section: Hyperactivity Following Picrotoxin Infusion Into the Ventralmentioning
confidence: 88%
“…Whereas in particular grooming had a strong effect, gross postural changes, such as turning, did not affect startle and PPI (Wecker and Ison 1986). Picrotoxin infusion into the ventral hippocampus induced increased locomotor activity, which results from gross postural changes, while there was no evidence of increased grooming.…”
Section: Hyperactivity Following Picrotoxin Infusion Into the Ventralmentioning
confidence: 92%
“…(100 nM in 5 l; Frankland et al, 1996). Because decreases in motor activity are associated with increases in startle amplitudes (Wecker and Ison, 1986;Plappert et al, 1993), it is necessary to test whether drug infusions have nonspecific effects on locomotor activity in experiments such as these. However, we found that similar doses of pentagastrin had no effect on locomotor activity over a similar time course.…”
Section: Discussionmentioning
confidence: 99%
“…To control for the possibility that increases in startle amplitudes result from decreases in motor activity (Wecker and Ison, 1986;Plappert et al, 1993), in Experiment 2 we tested whether similar intra-amygdala infusions of pentagastrin affect locomotor activity. A randomly selected subset (n ϭ 24) of rats tested for startle in Experiment 1 was used in this experiment.…”
Section: Experiments 2: Effect Of Intra-amygdala Infusions Of Pentagasmentioning
confidence: 99%